Evaluasi Penyelenggaraan Pemilu Di Indonesia Dan Peningkatan Partisipasi Masyarakat Digital Untuk Mewujudkan Pemilu Berintegritas - Surya Ningsih (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
A simultaneous election election is an election that has a high degree in the election for both the election and the bawaslu. Elections are expected to be held under regulations of the regulations of the regulation of the ethics of the organizers. In addition to voting for presidents and vice presidents, the 2019 elections also voted for parliament, DPD, provincial office, and county council. Thus, the burden of electoral arrangements can be identified from the start and the minimized risk measures unwelcome. Then it should be equally important to evaluate the integrity of the electorate, thus achieving a common, integrity elections. The writing is trying to provide a solution to the upcoming 2024 elections, to reflect the 2019 elections.